2003
DOI: 10.1177/0095399703257218
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Bioequivalence of Levofloxacin When Coadministered with a Mineral‐Fortified Breakfast of Juice and Cereal

Abstract: Previous studies have demonstrated that the chelation interactions demonstrated between fluoroquinolones and antacids also occur when they are coadministered with mineral-fortified foods. This study was conducted to evaluate the bioequivalence of levofloxacin when administered in a fasting state as compared to when it was administered with a common breakfast of calcium-fortified orange juice and ready-to-eat cereal. Fourteen of 16 healthy volunteers completed this study and received 500 mg of levofloxacin with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
(57 reference statements)
1
10
0
2
Order By: Relevance
“…Mean values for pharmacokinetic parameters C max (reference: 5.69 µg/mL; test: 5.67 µg/mL), T max (reference: 1.60 h; test: 1.29 h), AUC 0-t (reference: 41.52 µg·h/mL; test: 39.22 µg·h/mL), AUC 0-inf (reference: 45.50 µg·h/mL; test: 44.24 µg·h/mL) and T 1/2el (reference: 6.55 hours; test: 6.69 hours) were similar to that reported by other authors (Amsden, Whitaker, Johnson, 2003;Chien et al, 1997;Lee et al, 1997;Lubasch et al, 2000;Wagenlehner et al, 2006). ANOVA revealed the absence of sequence effect for C max , AUC 0-t e AUC 0-inf .…”
Section: Discussionsupporting
confidence: 90%
“…Mean values for pharmacokinetic parameters C max (reference: 5.69 µg/mL; test: 5.67 µg/mL), T max (reference: 1.60 h; test: 1.29 h), AUC 0-t (reference: 41.52 µg·h/mL; test: 39.22 µg·h/mL), AUC 0-inf (reference: 45.50 µg·h/mL; test: 44.24 µg·h/mL) and T 1/2el (reference: 6.55 hours; test: 6.69 hours) were similar to that reported by other authors (Amsden, Whitaker, Johnson, 2003;Chien et al, 1997;Lee et al, 1997;Lubasch et al, 2000;Wagenlehner et al, 2006). ANOVA revealed the absence of sequence effect for C max , AUC 0-t e AUC 0-inf .…”
Section: Discussionsupporting
confidence: 90%
“…We also found that the incidence of infectious complications was reduced further when patients were instructed thoroughly about the use of their prophylactic antimicrobial medications. Because mineral-fortified meals or drinks may interfere with the absorption of fluoroquinolones [30], it is important to let patients know the factors of which they should be aware in their use of these medications.…”
Section: Discussionmentioning
confidence: 99%
“…Orange juice supplemented with calcium may lead to the formation of chelate with fl uoroquinolones (ciprofl oxacin, gatifl oxacin, levofl oxacin) and tetracyclines (tetracycline, minocycline). Th e www.hophonline.org administration of levofl oxacin with food-rich calcium signifi cantly reduces its bioavailability [45]. Calcium also prevents the bisphosphonate absorption.…”
Section: Minerals and Calciummentioning
confidence: 99%